FORMULATION OF CREAM BODY SCRUB FROM ETHANOL EXTRACT OF CASSAVA LEAVES (Manihot esculenta) AS ANTIOXIDANT - Malik, Fadhliyah; Suryani, Suryani; Ihsan, Sunandar; Meilany, Elvianti; Hamsidi, Rini (Journal of Vocational Health Studies, 2020)
Background: Plant cassava leaves (Manihot esculenta) are known flavonoid is efficacious as antioxidant. Antioxidant can prevent damage to the skin by reducing free radical activity. Purpose: The purpose of this study to determine the concentration of ethanol extract of leaves of cassava can be formulated into dosage cream body scrub which have antioxidant activity. Method: Cassava leaf extract obtained by maceration using 97% ethanol. Determination of antioxidant activity by the method of reduction of free radical DPPH (1,1-diphenyl-2-picryl-hydrazyl). Result: The ethanol extract of cassava leaves are formulated into dosage cream body scrub with concentration variations 0,0085 mg/mL  (formula 1), 0,017 mg/mL  (formula 2), and 0,0255 mg/mL  (formula 3). Stability test preparation cream body scrub using cycling tests performed for 6 cycles. Preparation cream body scrub to formula I has a moderate antioxidant activity with IC50 158,16 µg/mL, formula 2 has an active antioxidant activity with IC50 66,59 µg/mL, and formula 3 has a stronger antioxidant activity with IC50 38,80 µg/mL. Conclusion: Cream body scrub and cassava ethanol extract does not irritate so it is safe to use. Preparations cream body scrub well have the most activity at a concentration of 0,0255 mg/mL with IC50 38,80 µg/mL.